(untitled) (Research, Society and Development, 2022)
The objective of this research is to analyze the relation between the STEM Movement and Large Scale Assessments in the Brazilian educational scope (Basic Education Assessment System - SAEB, National Exam for Certification of Competence in Youngsters and Adults - ENCCEJA and High School National Exam - ENEM), verifying the influences, approximations and disengagements between the two terms as presented on the normatives documents. To this end, the methodological strategy is a qualitative investigation, with descriptive-exploratory character in the matrix of references of ENEM, SAEB and ENCCEJA. For the analyses, it will be used the Content Analysis on the structural categories of the STEM Movement: Emancipatory Teaching, Levels of Integration, Formation for the World of Work, Problem Resolution, Creativity, Criticality, Communication and Collaboration. As the results it was found that criticality is present in all documents, while creativity and collaboration are not contemplated in any of these documents. Communication is addressed in only one area of the ENEM and ENCCEJA assessments, and it is not present in the SAEB’s matrix. Moreover, emancipatory teaching and formation for the world of work timidly appears in ENEM and ENCCEJA, being ausent of SAEB. The resolution of real situations is oriented in all documents. The levels of integration make themselves present only at a disciplinary level. Therefore, none of the three Brazilian large scale assessments effectively evaluate all primordial points to STEM Education. So, it is necessary an evaluation to analyze its positive and negative effects, as well as if its real perspective is being contemplated.